FcγRIIB engagement drives agonistic activity of Fc-engineered αOX40 antibody to stimulate human tumor-infiltrating T cells. Issue 2 (7th September 2020) - Campos Carrascosa, Lucia; van Beek, Adriaan A; de Ruiter, Valeska; Doukas, Michail; Wei, Jie; Fisher, Timothy S; Ching, Keith; Yang, Wenjing; van Loon, Karlijn; Boor, Patrick P C; Rakké, Yannick S; Noordam, Lisanne; et al.
Abstract : Background: OX40 (CD134) is a costimulatory molecule of the tumor necrosis factor receptor superfamily that is currently being investigated as a target for cancer immunotherapy. However, despite promising results in murine tumor models, the clinical efficacy of agonistic αOX40 antibodies in the treatment of patients with cancer has fallen short of the high expectation in earlier-stage trials. Methods: Using lymphocytes from resected tumor, tumor-free (TF) tissue and peripheral blood mononuclear cells (PBMC) of 96 patients with hepatocellular and colorectal cancers, we determined OX40 expression and the in vitro T-cell agonistic activity of OX40-targeting compounds. RNA-Seq was used to evaluate OX40-mediated transcriptional changes in CD4+ and CD8+ human tumor-infiltrating lymphocytes (TILs). Results: Here, we show that OX40 was overexpressed on tumor-infiltrating CD4+ T cells compared with blood and TF tissue-derived T cells. In contrast to a clinical candidate αOX40 antibody, treatment with an Fc-engineered αOX40 antibody (αOX40_v12) with selectively enhanced FcγRIIB affinity, stimulated in vitro CD4+ and CD8+ TIL expansion, as well as cytokine and chemokine secretions. The activity of αOX40_v12 was dependent on FcγRIIB engagement and intrinsic CD3/CD28 signals. The transcriptional landscape of CD4+ and CD8+ TILs shifted toward a prosurvival, inflammatory and chemotactic profile on treatment with αOX40_v12. Conclusions: OX40 is overexpressed on CD4+ TILs and thus represents a promising target for immunotherapy. Targeting OX40 with currently used agonistic antibodies may be inefficient due to lack of OX40 multimerization. Thus, Fc engineering is a powerful tool in enhancing the agonistic activity of αOX40 antibody and may shape the future design of antibody-mediated αOX40 immunotherapy.